English: A Senior Course - Yatel, G. (Kiev State Text-Book Publishing House, 1959)
The book was intended to meet the needs of the third and fourth year students for foreign languages at pedagogical institutes and universities (students of English by correspondence including). As it was designed as a comprehensive senior course of English, the book includes both analytical and synthetic reading texts.
Keywords: EFL